A modified theta projection model for the creep behaviour of creep-resistant steel. (August 2018) - Song, Ming; Xu, Tong; Wang, Qijiang; Wang, Weilian; Zhou, Yedong; Gong, Min; Sun, Chao
Abstract: A modified theta projection model is proposed for the description of creep behaviour. The model shows very good flexibility in fitting the entire test data of the creep-resistant steel 12Cr1MoV over the three creep stages. The capability of describing the primary to secondary stage makes it easier to precisely evaluate the steady state or minimum creep rate using the model. The model is derived and modified from the original theta projection method. It also keeps the four indeterminate coefficients and can meet the convergence condition easily during regression by the least squares method. In this paper, the minimum creep rates of 12Cr1MoV are also obtained and discussed. Highlights: A modified theta projection model is proposed for the creep behaviour description. The model shows very good flexibility in fitting the entire creep data over the three stages. The minimum creep rate can be precisely determined by the this model.